Rekam Jejak Muslim Rohingya di Myanmar - Tati Hartimah (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2010)
Rohingya tribe lived in jungles spread in Araka, Myanmar since 8th century, were Muslim. they were considered as the second class citizen came from Banglades, treated inequally, and rejected to be part of country. this condition continued from 18th century up to now. this condition is a result of Burma ethnic domination (Tibeto-Burmans) which then became the militery regime. through Rohingya Solidarity Organization (RSO) established in 1980, Arakan Rohingya Islamic Front (ARIF) established in 1987, and Rohingya National alliance (RNA), the tribe has started to go againts the regime.